Detecting eating psychopathology in female athletes by asking about exercise: use of the Compulsive Exercise Test - Plateau, C.R.; Arcelus, Jon; Meyer, C. (Wiley, 2017)
The present study assessed the suitability of the Compulsive Exercise Test (athlete version; CET-A) for identifying female athletes with clinically significant features related to or comparable with eating psychopathology. Three hundred and sixty-one female athletes (including 12 with a clinically diagnosed eating disorder) completed the Eating Disorders Examination Questionnaire (EDE-Q) and the CET-A. Receiver Operating Curve (ROC) analysis was employed to identify a cut-off value on the CET-A which could indicate clinically significant features related to or comparable with eating psychopathology among female athletes. The analysis demonstrated that a CET-A score of 10 successfully discriminated female athletes with a current eating disorder. The results suggest that the CET-A may be a suitable tool for detecting eating psychopathology in female athletes. Additional longitudinal research is needed to evaluate the predictive value of the CET-A.